2012
DOI: 10.1007/s11250-012-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, digestibility, and voluntary feed intake of mango residues by sheep

Abstract: The chemical composition, digestibility, and voluntary feed intake by sheep of mango by-products were studied in an experiment with five dietary treatments consisting of mango peels and seed kernels, offered individually or together with urea block and a control. The mango residues were offered with rice straw and the control diet was straw only. Five groups of five male sheep of Djallonké type, 12-18 months old and weighing on average 18.6 kg were allocated randomly to the diets to assess the voluntary feed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The effects of feeding MB including avocado wastes to goats on milk yield and composition have been recently studied [10], but to our best knowledge, there is no information on the possibility of including mango wastes in MB. However, several studies have investigated the direct feeding of mango wastes to ruminants [11][12][13] and non-ruminants [14,15], indicating that they can be used as alternative feeds [16]. The aim of this study was therefore to assess the chemical composition and in vitro ruminal fermentation of two type of wastes from avocado and mango, peels and a mixture of pulp and peels (PP), and to analyze the in vitro ruminal fermentation of MB including PP wastes of each fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of feeding MB including avocado wastes to goats on milk yield and composition have been recently studied [10], but to our best knowledge, there is no information on the possibility of including mango wastes in MB. However, several studies have investigated the direct feeding of mango wastes to ruminants [11][12][13] and non-ruminants [14,15], indicating that they can be used as alternative feeds [16]. The aim of this study was therefore to assess the chemical composition and in vitro ruminal fermentation of two type of wastes from avocado and mango, peels and a mixture of pulp and peels (PP), and to analyze the in vitro ruminal fermentation of MB including PP wastes of each fruit.…”
Section: Introductionmentioning
confidence: 99%
“…It is a typical multipurpose tree for its industrial and medicinal applications, which has significant economic values. Mango kernels and peels can be used in animal diets as sources of starch or protein [4,5]. Mango leaves have high content of phenolic compounds containing mangiferin, flavonoids, benzophenone, and gallotannins [6].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have developed feeding strategies that guarantee the sustainability of livestock production systems based on local feed sources [1]. Several reports have shown that tropical fruit by-products can be used as animal feed to replace cereal-based concentrates without negatively affecting animal production performance [1], such as mango residues in sheep [2], tomato and cucumber waste fruits in dairy goats [3], and longan residues in cattle [4]. Moreover, many of these by-products are largely wasted or unused [5].…”
Section: Introductionmentioning
confidence: 99%